SUPERNOVAE EXPLOSIONS THEORY AND COMPACT REMNANT OF SN 1987A - Chechetkin, V. M.; Baranov, A. A.; Popov, M. V.; Lugovsky, A. Yu. (Одеські астрономічні публікації, 2012)
Hydrodynamics of massive star explosion within a non-spherical supernova model is presented. The explosive burning is computed in the He-core of a progenitor. It is assumed that the iron core and the other layers of the intermediate-mass nuclei formed a compact central object beyond the mass cut and its formation did not disturb the stellar envelope. A Piecewise Parabolic Method on a Local stencil (PPML) is applied to simulate the hydrodynamics of the explosion. The problem of compact remnant creation after the explosion is discussed in relation with SN 1987A observations. The computations show that at the neighbourhood of compact remnant a significant quantity of the matter should remain. The accretion of this matter to the compact remnant should produce strong radiation which is not observed in the case of SN 1987A.